Helicobacter pylori and gastritis in patients with peptic ulcer and non-ulcer dyspepsia: ethnic differences in Singapore. Issue 8 (August 1990) - Kang, J Y; Wee, A; Math, M V; Guan, R; Tay, H H; Yap, I; Sutherland, I H
Abstract : Peptic ulcer occurs with different frequencies in the three main racial groups in Singapore. This study aimed firstly to determine the prevalence of Helicobacter pylori in peptic ulcer and non-ulcer dyspepsia patients of the different races and secondly, to assess the relation between H pylori, histological gastritis, patient diagnosis, and race. Gastric antral biopsy specimens from 1502 patients undergoing gastroduodenoscopy were studied and 892 (59%) were positive for H pylori. H pylori was strongly associated with gastritis: 873 of 1197 (73%) patients with gastritis were positive compared with 19 of 305 (6%) without gastritis (p less than 0.0001). The prevalences of H pylori and gastritis were similar in peptic ulcer patients of different races. Malay patients with non-ulcer dyspepsia, however, were less likely to be positive for H pylori (10 of 46 (22%] or to have antral gastritis (17 of 46 (37%] than Chinese (292 of 605 (48%) were positive for H pylori and 421 of 605 (70%) had gastritis) and Indians (35 of 61 (57%) were H pylori positive and 42 of 61 (69%) had gastritis). Patients with duodenal ulcer were more likely to be positive for H pylori than those with non-ulcer dyspepsia, even when subjects with gastritis were considered separately. While our results do not help to explain the observed racial differences in peptic ulcer frequency it may be that the pathophysiology of non-ulcer dyspepsia is different in the different races in Singapore.